Pengaruh Online Visual Merchandising dan Flash Sale Terhadap Impulse Buying Pengguna Tiktok Shop Live Streaming - Michael Tinambunan; Rudy P. Tobing (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
The development of information and communication technology has encouraged changes in consumer behavior, especially in online shopping activities through social commerce platforms such as TikTok shop live streaming. So an effective marketing strategy is needed, such as maximizing product visualization and attractive promotional offers to attract consumer attention and increase competitiveness in the digital market. This research aims to analyze the influence of online visual merchandising and flash sales on the impulse buying of TikTok shop live streaming users on the 3Second brand. Design/methodology/approach: The research uses quantitative methods with associative research type with a sample size of 100 respondents selected using a simple random sampling method from the population of followers of the TikTok account @its3second. Instrument quality testing includes validity testing and reliability testing. Data analysis uses descriptive analysis. Meanwhile, for hypothesis testing, multiple linear regression analysis is used. Results: The research results show that the online visual merchandising and flash sale variables have a positive and significant influence on the impulse buying of TikTok shop live streaming users on the 3Second brand with an R-Square value of 0.515. Research limitations/Implications: Research limitations lie in the method of collecting data through online questionnaires which has the potential to be biased and the implications of the research are encouraging increased product displays and flash sale strategies in live streaming marketing to increase interaction and purchases.